RehabilitacjaDoes the cardiac rehabilitation is essential in the age of modern invasive cardiology and cardiac surgery? - Dylewicz, Piotr; Borowicz-Bieńkowska, Sławomira (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
cardiological rehabilitation, rehabilitation in cardiac surgery, physical training.